Localised delivery of doxorubicin to prostate cancer cells through a PSMA-targeted hyperbranched polymer theranostic. (October 2017) - Pearce, Amanda K.; Simpson, Joshua D.; Fletcher, Nicholas L.; Houston, Zachary H.; Fuchs, Adrian V.; Russell, Pamela J.; Whittaker, Andrew K.; Thurecht, Kristofer J.
Abstract: The therapeutic potential of hyperbranched polymers targeted to prostate cancer and loaded with doxorubicin was investigated. Polyethylene glycol hyperbranched polymers were synthesised via RAFT polymerisation to feature glutamate urea targeting ligands for PSMA on the periphery. The chemotherapeutic, doxorubicin, was attached to the hyperbranched polymers through hydrazone formation, which allowed controlled release of the drug from the polymers in vitro endosomal conditions, with 90% release of the drug over 36 h. The polymers were able to target to PSMA-expressing prostate cancer cells in vitro, and demonstrated comparable cytotoxicity to free doxorubicin. The ability of the hyperbranched polymers to specifically facilitate transport of loaded doxorubicin into the cells was confirmed using live cell confocal imaging, which demonstrated that the drug was able to travel with the polymer into cells by receptor mediated internalisation, and subsequently be released into the nucleus following hydrazone degradation. Finally, the ability of the complex to induce a therapeutic effect on prostate cancer cells was investigated through a long term tumour regression study, which confirmed that the DOX-loaded polymers were able to significantly reduce the volume of subcutaneous prostate tumours in vivo in comparison to free doxorubicin and a polymer control, with no adverse toxicity to the animals. This work therefore demonstrates the potential of a hyperbranched polymer system to be utilised for prostate cancer theranostics.